Promosi Kesehatan Gigi Menggunakan Media Smart Audio Toothbrush With UV-Filtered Toothpaste Dispenser (Ada’s Toothbrush) Terhadap Pengetahuan Siswa Sekolah Luar Biasa - Adawiyyah, Evi (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Children with special needs generally have suboptimal dental hygiene. Therefore, dental and oral health education is an important step in improving their health, especially among visually impaired children. One medium that is considered quite effective for use with visually impaired children is Ada's Toothbrush, which is designed to suit their characteristics and needs. This study aims to evaluate the extent to which the Ada's Toothbrush can improve visually impaired children's knowledge about how to brush their teeth. This study uses a pre-experimental research design with a one group pretest–posttest model, involving 30 visually impaired children selected through total sampling technique. Data analysis was performed using the Shapiro–Wilk normality test, followed by the Wilcoxon test. The statistical test results showed a significant increase in knowledge after the intervention, with a p-value of 0.000 (p < 0.05). These findings confirm that the use of the Smart Audio Toothbrush With UV-Filtered Toothpaste Dispenser is effective in improving visually impaired children's understanding of how to brush their teeth, both at the Semarang State Special School and at the A Dria Adi Special School in Semarang City.   Keywords: Health promotion; children with special needs; visually impaired children; knowledge of tooth brushing